The NOTECHS+: A Short Scale Designed for Assessing the Non-technical Skills (and more) in the Aviation and the Emergency Personnel - Ceschi, Andrea; Costantini, Arianna; Zagarese, Vivian; Avi, Eleonora; Sartori, Riccardo (Frontiers in Psychology, 2019)
This project aims to develop an instrument using a quali-quantitative methodology to measure the Non-Technical Skills (i.e., NOTECHS), and Resilience and Emotion Regulation, in a sector that comprises the aviation and the emergency personnel: the Helicopter Emergency Medical Service (HEMS). The design process of the scale was carried out starting from a review on the behavioral markers used to detect the NOTECHS. Moreover, 70 interviews with HEMS experts have been conducted with the aim of developing Resilience and Emotion Regulation items. Next, through a pre-assessment procedure, a Q-Sort test was performed on a sample of students (N=30) to test the logical principles, but also intelligibility and clarity of the scale developed. Once the instrument was defined, 211 subjects from the HEMS sector were surveyed to test the theoretical model behind the NOTECHS+ instrument. First exploratory and then the confirmatory analysis yielded a solution that suggested that these items conform to a bi-factor model composed of three skill-dimensions: Social skills (i.e., Cooperation and Leadership and Managerial skills), Cognitive skills (i.e-., Decision-Making and Situation Awareness) and Emotional skills (i.e., Resilience and Emotional Regulation). Finally, the study ends up with a discussion on the results obtained, including practical implications on assessment and training based on such a new instrument.